For making a declaration of countermeasures against the falling birth rate from the Japanese Society for Hygiene: summary of discussion in the working group on academic research strategy against an aging society with low birth rate - Kyoko Nomura; Kanae Karita; Atsuko Araki; Emiko Nishioka; Go Muto; Miyuki Iwai-Shimada; Mariko Nishikitani; Mariko Inoue; Shinobu Tsurugano; Naomi Kitano; Mayumi Tsuji; Sachiko Iijima; et al. (Komiyama Printing Co. Ltd, 2019)
Abstract In 1952, the Japanese Society for Hygiene had once passed a resolution at its 22nd symposium on population control, recommending the suppression of population growth based on the idea of cultivating a healthier population in the area of eugenics. Over half a century has now passed since this recommendation; Japan is witnessing an aging of the population (it is estimated that over 65-year-olds made up 27.7% of the population in 2017) and a decline in the birth rate (total fertility rate 1.43 births per woman in 2017) at a rate that is unparalleled in the world; Japan is faced with a "super-aging" society with low birth rate. In 2017, the Society passed a resolution to encourage all scientists to engage in academic researches to address the issue of the declining birth rate that Japan is currently facing. In this commentary, the Society hereby declares that the entire text of the 1952 proposal is revoked and the ideas relating to eugenics is rejected. Since the Society has set up a working group on the issue in 2016, there have been three symposiums, and working group committee members began publishing a series of articles in the Society's Japanese language journal. This commentary primarily provides an overview of the findings from the published articles, which will form the scientific basis for the Society's declaration. The areas we covered here included the following: (1) improving the social and work environment to balance between the personal and professional life; (2) proactive education on reproductive health; (3) children's health begins with nutritional management in women of reproductive age; (4) workplace environment and occupational health; (5) workplace measures to counter the declining birth rate; (6) research into the effect of environmental chemicals on sexual maturity, reproductive function, and the children of next generation; and (7) comprehensive research into the relationship among contemporary society, parental stress, and healthy child-rearing. Based on the seven topics, we will set out a declaration to address Japan's aging society with low birth rate.